Geographical and ethnic differences of osteoarthritis-associated hip and knee replacement surgeries in New Zealand: a population-based cross-sectional study - Chunhuan Lao; David Lees; Sandeep Patel; Douglas White; Ross Lawrenson (BMJ Open)
Objectives To (1) explore the regional and ethnic differences in rates of publicly funded osteoarthritis-associated hip and knee replacement surgeries and (2) investigate the mortality after surgery.Design Population-based, retrospective, cross-sectional study.Setting General population in New Zealand.Participants Patients with osteoarthritis who underwent publicly funded primary hip and knee replacement surgeries in 2005–2017. Patients aged 14–99 years were included.Primary and secondary outcome measures Age-standardised rate, standardised mortality ratio (SMR) and 30 days, 90 days and 1 year mortality.Results We identified 53 439 primary hip replacements and 50 072 primary knee replacements with a diagnosis of osteoarthritis. The number and age-standardised rates of hip and knee replacements increased over time. Māori had the highest age-standardised rate of hip replacements, followed by European/others and Pacific, and Asian had the lowest rate. Pacific had the highest age-standardised rate of knee replacements, followed by Māori and European/others, and Asian had the lowest rate. The Northern Health Network had the lowest rate of hip surgeries, and the Southern Health Network had the lowest rate of knee surgeries. The SMRs of patients undergoing hip and knee replacements were lower than the general population: 0.92 (95% CI 0.89 to 0.95) for hip and 0.79 (95% CI 0.76 to 0.82) for knee. The SMRs were decreasing over time. The patterns of 30 days, 90 days and 1 year mortality were similar to the SMR.Conclusions The numbers of publicly funded osteoarthritis-associated primary hip and knee replacements are steadily increasing. Māori people had the highest age-standardised rate of hip replacements and Pacific people had the highest rate of knee replacements. The Northern Health Network had the lowest rate of hip surgeries, and the Southern Health Network had the lowest rate of knee surgeries. Compared with the general population, patients who had hip and knee replacements have a better life expectancy.